Managing change process: A case study of a private school in Sharjah - AL BAKRI, NADA RAFEA ASAAD (2016)
Change process management is considered nowadays as one of the most important indicators of success and progress in societies. Due to the fact that most school administrations face a lot of difficulties and challenges concerning the management process, it becomes necessary for them to adopt a real change and work on the possible ways to achieve this change. The significance of change process management increases as the modern world trends of education and learning require a change. However, change needs the leadership to engage in organized and planned efforts to achieve the sought after goals. These efforts include utilizing a proper scientific employment policy of human and material resources, using technology in the educational organizations, and creating motivation among workers to participate and cooperate in making decisions. This paper examines the importance of implementing a managing change process and how the effective change is managed in private schools in the United Arab Emirates. The study investigates the effect of motivation, teacher and parents’ inclusion in making decisions, and job satisfaction on the success of such a change project. The study also proposes a model that would accomplish the management of a change process in private schools. To achieve the objectives of the study a case study was carried out in a private school in Sharjah. In addition, a concurrent mixed-methods approach was adopted to select the research instruments which consisted of questionnaires distributed to teachers and parents as well as semi-structured interviews conducted with the principal and decision makers. The purpose of the questionnaires was to collect as large numbers as possible of teachers and parents’ viewpoints about job satisfaction, teachers’ inclusion in decisions making, and parents involvement in the management process. The semi-structured interviews were carried out to elicit the perspectives of the principal and decision makers towards change process management. The findings confirmed that when job satisfaction is achieved and teachers and parents are motivated and involved in the managing process then the effective and fruitful management of the change process will be achieved .The research recommends the importance of acquiring successful change process management treatments around the world to get benefits from positives and leave the negatives, so that we can reach globalization, and achieve the UAE vision and mission towards education.